Exploring Consumer Behavior in Maritime Transportation: Price, Facilities, And Timeliness Factors Impacting Purchasing Decisions on The Semarang – Lampung Ship Route - Rahmasari, Lisda (Research Horizon, 2024)
Transportation plays an important role in supporting community activities amidst globalization. This research focuses on users of roll-on/roll-off (RORO or ro-ro) ship services which traverse the Semarang – Lampung route. By using a sample of 100 respondents, non-probability sampling via purposive sampling was used. Data collection involves administering questionnaires to measure respondents' perspectives on the variables studied. Multiple linear regression analysis was used for data analysis. The research results show that there is a positive and significant influence of price, facilities and timeliness factors on purchasing decisions. The regression equation obtained from this analysis highlights the interaction between these factors and purchasing behavior. Specifically, the results of this study highlight the individual impact of price, facilities, and timeliness on purchasing decisions in the context of ship services. These findings contribute to a deeper understanding of consumer behavior in transportation services, providing insights for service providers to tailor offerings that align with customer preferences and increase overall satisfaction.